Fair Values, Income Measurement, and Bank Analysts' Risk and Valuation Judgments - Hirst, D. Eric; Hopkins, Patrick E.; Wahlen, James M. (The Accounting Review, 2004)
We examine how fair-value-income measurement affects commercial bank equity analysts' risk and value judgments. Normatively, holding information and other underlying economics constant, bank analysts' risk and valuation assessments should distinguish between banks with different risks, but should not depend on how banks measure income. In our experiment, we vary income measurement—full-fair-value (all fair-value changes recognized in income) versus piecemeal-fair-value (some fair-value changes recognized in income, others disclosed in the notes). We also vary interest-rate-risk exposure (exposed versus hedged). We find that bank analysts' risk and value judgments distinguish banks' exposure to interest-rate risk only under full-fair-value-income measurement. Our evidence contributes to research concerned with financial performance reporting, risk, and fair-value accounting by demonstrating that differences in income measurement affect fundamental judgments of specialist analysts. Our findings are striking because they: (1) point toward an important role for measurement and recognition of fair-value gains and losses in income, and (2) suggest that note disclosure is not a substitute for financial-statement recognition (even for professional analysts specializing in banks and working in a context that involves assessment of core operations of a bank). These results should be of interest to accounting standard setters as they evaluate whether to require full-fair-value-income measurement.